(untitled) (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2025)
Employees’ perspectives of the company’s social responsibility (SR) and the company’s SR impact on employees have so far been given little attention in research. This gap is surprising since it is well known to what extent employees affect overall companies’ results. They have a crucial role in SR activities implementation, so it is important for management to define employees’ roles in SR activities implementation carefully. This paper explored the influence of employees’ participation in SR activities on their affective commitment to service companies. The main hypothesis was that participation in SR activities has a significant positive impact on employees’ affective commitment. The goal was to show that employees who participated in SR activities were more committed than employees who did not participate in SR activities. The data were collected through a questionnaire and analysed using descriptive statistics, independent-samples t-tests, and one-way ANOVA. The results showed that there were no statistically significant differences in the level of affective commitment between employees who participated in SR activities and those who did not participate in them. Less than half of respondents participated in SR activities, so a suggestion for managers was to share the positive experience of participation in SR activities and invite employees to participate more.